TEKNIK PENYADAPAN PINUS UNTUK PENINGKATAN PRODUKSI MELALUI STIMULAN HAYATI - Sukadaryati; Dulsalam (Jurnal Penelitian Hasil Hutan, 2025)
The increased demand of pine resin both for domestic and overseas markets has necessitated efforts to enhance pine-sap production. The use of strong acid-based conventional stimulants has been long employed by Perum Perhutani, but questions arise regarding the environment effect as well as growth survival of the tapped pine trees. Consequently, the use of biostimulant deserves thorough consideration, since not only will assure friendly-environmental effects but also securing the sustainability of the pine trees. An experiment was conducted to look into the effect of using biostimulants on the production of sap (exudates) from the tapped pine trees. Three tapping techniques were employed, i.e. mujitech, boring and kedukul. The biostimulant consisted of three kinds (lengkuas, kencur, and red onion), each with three concentration levels (50%, 75%, and 100%). It turned out different tapping techniques seemed not affecting the pine-sap production, nor did the effect of biostimulant concentrations (50-100%). However, different kinds of biostimulants did so, whereby lengkuas afforded the sap-yield increase the highest (268%) compared to the control (without biostimulants), followed in order by kencur (206%) and red onion (180%). Use of the second and third caused no significant difference. Economically, the use of biostimulant at 50% concetration was effective enough. Further attempts are neseccary to find other alternative biostimulants.